A single session of moderate exercise, without energy deficit, may reduce svcam-1 concentrations in young, sedentary females - Krause, Molly Annamarie, author; Melby, Christopher, advisor; Hickey, Matthew, committee member; Nelson, Tracy, committee member (Colorado State University. Libraries, 2010)
Purpose: Cardiovascular disease remains the number one cause of death within the United States and globally [1, 2]. Postprandial lipemia and vascular adhesion molecules are becoming more widely recognized as biomedical makers associated with increased risk of developing CVD [3-5]. It has been well established that moderate exercise can improve some aspects of postprandial metabolism such as decreased triglycerides and improved insulin sensitivity [6]. However, there is limited data regarding the effect of prior moderate exercise on attenuating postprandial response specific to adhesion molecules [7, 8]. The purpose of this study was to determine the effects of a single bout of acute exercise, with energy replacement, on plasma soluble vascular adhesion molecule-1 (sVCAM-1), a marker of endothelial dysfunction, measured during fasting and in response to a high-fat, high-carbohydrate meal in young, non-obese, sedentary females. Methods: Eight, non-obese (x body mass index=24.6 kg/m2), habitually sedentary females (x age= 19.6 y) participated in this study. Following preliminary testing, each subject completed two trials in random order: 1) Exercise (Ex) 2) Non-exercise (Non-Ex). Each trial took place over 2 days. On the evening of day 1, subjects either rested (Non-Ex) or completed a cycle ergometer exercise bout at 65% peak heart rate, eliciting net exercise energy expenditure of ~285kcalories. On the morning of day 2 of each trial a fasting venous blood sample was drawn for measurement of sVCAM-1, followed by the consumption of a high-fat, high-sugar meal by each participant. Postprandial venous blood samples were then taken over at 2, 4, and 6 hours following meal ingestion for measurement plasma sVCAM-1 concentrations. Results: There was no significant treatment by time interaction on sVCAM-1 concentrations, nor was there a significant main effect of time. There was a significant condition effect on circulating soluble VCAM-1 concentrations such that concentrations were lower before and following the high-fat, high-sugar meal challenge for the EX compare to the NonEx condition. Conclusions: Results from the current study suggest that a single session of moderate exercise, without an energy deficit, may reduce sVCAM-1 concentrations in young, sedentary females. However, this finding must be viewed with caution owing to possible issues with thesVCAM-1 measurements, and the assay repeated prior to drawing any conclusions about the effect of acute exercise on circulating sVCAM-1 concentrations measured the morning after exercise.
Keywords: sVCAM-1; females; exercise; energy deficit; adhesion molecules; Cell adhesion molecules; Sedentary women; Young women -- Nutrition